Intra-amniotic infection and sterile intra-amniotic inflammation in women with preterm labor with intact membranes are associated with a higher rate of Ureaplasma species DNA presence in the cervical fluid. (12th December 2022) - Kacerovsky, Marian; Stranik, Jaroslav; Kukla, Rudolf; Bolehovska, Radka; Bostik, Pavel; Matulova, Jana; Stepan, Martin; Hladky, Jan; Jacobsson, Bo; Musilova, Ivana
Abstract: Objective: To determine the prevalence of Ureaplasma spp. DNA and its load in the cervical fluid in women with preterm labor with intact membranes (PTL) complicated by intra-amniotic infection (the presence of both microbial invasion of the amniotic cavity and intra-amniotic inflammation) or sterile intra-amniotic inflammation (the presence of intra-amniotic inflammation alone). Methods: Overall, 115 women with singleton pregnancies complicated by PTL between gestational ages of 22 + 0 and 34 + 6 weeks were included in this study. Paired amniotic and cervical fluid samples were collected at the time of admission via transabdominal amniocentesis using a Dacron polyester swab. Microbial invasion of the amniotic cavity was diagnosed based on a combination of culture and molecular biology methods. Intra-amniotic inflammation was determined based on the concentration of interleukin-6 in the amniotic fluid. Bacterial and Ureaplasma spp. DNA loads were assessed in the cervical fluid using PCR. Results: Intra-amniotic infection and sterile inflammation were identified in 14% (16/115) and 25% (29/115) of the women, respectively. Ureaplasma spp. DNA in the cervical fluid was identified in 51% (59/115) of women. The presence of Ureaplasma spp. DNA in the cervical fluid was higher in women with intra-amniotic infection (75% (12/16)) and sterile intra-amniotic inflammation (76% (22/29)) than in women without intra-amniotic inflammation (36% (25/70); p  = .0002). Concurrent presence of Ureaplasma spp. and Mycoplasma hominis DNA was higher in women with intra-amniotic infection (42% (5/12)) than women with sterile intra-amniotic inflammation (7% (2/29)) and women without intra-amniotic inflammation (7% (5/70); p  = .001). There were no differences in the load of Ureaplasma spp. DNA in the cervical fluid among women with intra-amniotic infection, sterile intra-amniotic inflammation, and those without intra-amniotic inflammation (median values; infection: 1.2 × 10 4 copies DNA/mL; sterile: 5.0 × 10 5 copies DNA/mL; without: 8.4 × 10 4 copies DNA/mL; p  = .18). Conclusions: In PTL, both forms of intra-amniotic inflammation were associated with a higher prevalence of Ureaplasma spp. DNA in the cervical fluid. The presence of intra-amniotic infection was related to a higher rate of concurrent Ureaplasma spp. and M. hominis DNA in the cervical fluid.